Implementing sustainable agriculture : perceptions of hill-country farmers in the Rangitikei District : a thesis presented in partial fulfilment of the requirements for the degree of Master of Resource and Environmental Planning - King, Grant Frederick (Massey University, 1996)
This thesis investigates the perceptions concerning the implementation of sustainable agriculture in hill-country farming in New Zealand, primarily by using a survey of farmers from the Rangitikei District. A literature review identified three main groupings of approaches to sustainable agriculture: a production or economic based approach; a stewardship and intergenerational equity approach; and a social approach which emphasised social equity and rural community issues. It also stressed the importance of scale issues in sustainable agriculture with the analysis focussing on horizontal, vertical and temporal scales. It appears that the 'ideals' of sustainable agriculture as outlined in the literature are not being translated into reality in New Zealand, and indeed the ideals of New Zealand farmers may not correspond to those presented in the literature. A conceptual framework was constructed to further investigate this issue of the gap between the ideal end-state of sustainable agriculture and the actual practices. A survey of 260 'conventional' farmers in the high-terraces and hill-country of the Rangitikei was selected to empirically test the conceptual framework. The viewpoints of these farmers were contrasted with those of: a small sample of certified organic farmers who ran similar land-uses on similar land-classes; and a sample of professional staff who were selected from the regional councils, central government, industry groups, a farmer organisation, a conservation organisation, scientists and academic staff. A 78 question survey ascertained farmers ideals with regard to sustainable agriculture, what they considered to be desirable sustainable farming practices; what they considered to be barriers to sustainable agriculture; and what implementation methods (eg. regulation, education, rates rebates) they considered to be acceptable. The actual farmers practices (eg. pesticide use, fertiliser use, agroforestry, erosion control) were also surveyed using a relative scale which measured change over the last five years. The key findings of the sample survey were as follows. The overall preference for the 'hands-off' implementation methods, such as 'education' and 'further research' by all three groups. There was a lack of recognition of social characteristics of sustainable agriculture by the professional staff, compared to their acknowledgement of economic and environmental considerations. The practices undertaken by farmers had improved over the timeframe measured, although much of the change was for economic reasons as opposed to environmental considerations. The most commonly identified barriers by all the respondents were economic in nature. The thesis concluded with a discussion of the policy implications of research findings. The most important policy implication discussed was whether the preferred methods for implementing sustainable agriculture (ie. 'education' and 'further research') could actually overcome the perceived barriers to achieving sustainable agriculture which were predominantly economic in nature. Some further suggestions were also made on further research directions; most notably that the factors identified in the conceptual framework need to be tested on a wider range of farm-types and other regions in New Zealand.
Keywords: Sustainable agriculture; Rangitikei district, New Zealand; Hill country farming